2008
DOI: 10.1194/jlr.m800033-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-fat diet exposure during fetal life on type 2 diabetes development in the progeny

Abstract: Nutrition during fetal life is a critical factor contributing to diabetes development in adulthood. The aim of our study was to verify: 1) whether a high-fat (HF) diet in young adult mice induces alterations in beta-cell mass, proliferation, neogenesis, and apoptosis, as well as insulin sensitivity and secretion; 2) whether these alterations may be reversible after HF diet suspension; 3) the effects in a first (F1) and second generation (F2) of mice without direct exposure to a HF diet after birth. Type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 55 publications
(58 reference statements)
3
75
0
1
Order By: Relevance
“…A great increase in the number of TUNELpositive nuclei was observed after 60 days of HFD. Higher magnification of Hoechst-stained duodenal sections revealed intensely fluorescent nuclei, which is indicative of chromatin condensation, corresponding to the TUNELpositive nuclei (data not shown), as previously reported for HFD treatment for 30 and 90 days in mice [2]. Evidence for apoptosis was also confirmed by detection of fragmented DNA by ELISA; a progressive increase in optical density was found in the HFD rats compared with controls (375±86.3% vs 37±2.6% in control rats; data are optical density at 405 nm …”
Section: Glp-1-positive Cellsmentioning
confidence: 54%
See 1 more Smart Citation
“…A great increase in the number of TUNELpositive nuclei was observed after 60 days of HFD. Higher magnification of Hoechst-stained duodenal sections revealed intensely fluorescent nuclei, which is indicative of chromatin condensation, corresponding to the TUNELpositive nuclei (data not shown), as previously reported for HFD treatment for 30 and 90 days in mice [2]. Evidence for apoptosis was also confirmed by detection of fragmented DNA by ELISA; a progressive increase in optical density was found in the HFD rats compared with controls (375±86.3% vs 37±2.6% in control rats; data are optical density at 405 nm …”
Section: Glp-1-positive Cellsmentioning
confidence: 54%
“…The deranging effects of a high-fat diet (HFD) on beta cells, insulin secretion and insulin resistance have been extensively evaluated and documented by several research groups, including ours [1][2][3]. However, how HFD induces insulin resistance and diabetes is still unclear, and the major hypothesis that damage to mitochondria by fatty acids can be the primum movens in inducing glucose metabolism alteration has been disproved [4].…”
Section: Introductionmentioning
confidence: 99%
“…We purposely used a chow diet in the current study to establish that increased atherosclerosis in the offspring was due to in utero programming. The effect of programming on offspring may extend into the second generation: A recent high-fat diet programming study using mice showed that a high-fat diet leading to obesity during gestation produced glucose intolerance in both the first and second generations of offspring (41).…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have used animal models of high-fat or western style-diet-induced obesity (a diet that has increased fat and carbohydrate content) and have shown that maternal over-nutrition induces increased adiposity and induces permanent changes in metabolism in the offspring (72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84) . Using a similar Western diet, female Sprague-Dawley rats were started on the designated diet at 4 weeks of age.…”
Section: Animal Model Of Obesity In Pregnancy Induces Obesity In the mentioning
confidence: 99%